Multiple magma recharges over prolonged period ultimately trigger eruptions at Vulcano, Aeolian Islands - Marisa Giuffrida; Giuseppe Salerno; Marco Viccaro (Scientific Reports)
Abstract The compositional heterogeneity of clinopyroxene in products of the 1888-90 eruption at La Fossa of Vulcano has been used to constrain times of the plumbing system reactivation before the eruption. We have also investigated the temporal trend of the SO2 flux at La Fossa crater since 1978 to gather information about the origin, depths and quantity of magma involved in the recent degassing crises. Petrological data emphasizes migration of deep-seated magmas and their emplacement in the shallow system, clearly supporting the involvement of three distinct phases of mafic replenishments occurred respectively 85–140, 16–35 and 2–7 years before the 1888-90 eruption. These results reconcile with the dynamics of magma emplacement and degassing inferred for the recent periods of unrest. SO2 data for the period January 1978 – September 2024 imply a volume of intrusive magma of ~ 26–86 × 106 m3, which is comparable to the order of magnitude of magma volumes erupted during the 1888-90 cycle. Our petrological and geochemical data suggest that shallow reservoirs have been already largely pressurized by multiple mafic injections occurred over the last century.